Winter Food Habits and Preferences of Northern Bobwhites in East Texas - Donald R. Dietz Jr.; R. Montague Whiting Jr.; Nancy E. Koerth (National Quail Symposium Proceedings, 2017)
During late winter, 1994 and 1995, we investigated food habits and preferences of northern bobwhites (Colinus virginianus; hereafter, bobwhites) collected on forested lands in east Texas. Crops for bobwhites were collected from areas under 3 management regimes, namely intensively managed for bobwhites (QMA) (i.e., tree basal area reduced, annually burned, numerous multi-stage food plots, etc.), extensively managed for timber and wildlife (NBS) (i.e., burned every 3-5 years, scattered 2-stage food plots with corn feeders), and unmanaged for wildlife (i.e., burned every 5-7 years). With years pooled, partridge pea (Cassia fasciculata), Hercules club (Zanthoxylum clava-herculis), and pine (Pinus spp.) seeds, and clover leaflets (Trifolium spp.) comprised 93% by weight of foods of 79 bobwhites foods on QMA. On NBS, 81% of 40 bobwhite diets was butterfly pea (Centrosema virginianum), browntop millet, pine, wild bean (Strophostyles spp.), and corn seeds and clover leaflets; millet and corn were from food plots and feeders, respectively. For unmanaged areas, 79% of 19 bobwhite diets was butterfly pea, rush (Juncus spp.), pine, partridge pea, and American beautyberry (Callicarpa americana) seeds, and clover leaflets. Top-ranked food items on QMA were pine, hairy vetch, and Hercules club seeds in 1994 and butterfly pea, partridge pea, and wax myrtle (Myrica cerifera) seeds in 1995 (P < 0.05). On NBS, hawthorn (Crataegus spp.) and beautyberry seeds were top-ranked in 1994 as were kobe lespedeza, wild bean, and butterfly pea seeds in 1995. On unmanaged areas, butterfly pea and partridge pea seeds and clover leaflets were highest ranked in 1995. On forested lands, activities (e.g., disking, burning, establishing food plots) which provide seed-bearing plants, especially legumes, and clover greenery benefit bobwhites.
Keywords: Colinus virginianus; food availability; food habits; food preferences; Johnson’s rank method; northern bobwhite; PREFER